Carbon-isotope stratigraphy of shallow-water limestones and implications for the timing of Late Cretaceous sea-level rise and anoxic events (Cenomanian-Turonian of the peri-Adriatic carbonate platform, Croatia) - Davey, S; Jenkyns, H (1999)
A carbon-isotope stratigraphy of shallow-water Cretaceous limestones from the Adriatic/Dinaric carbonate platform, Croatia, has enabled accurate definition of the Cenomanian-Turonian boundary by reference to well-dated ammonite-bearing sections in England and the United States. The sediments close to the boundary show pelagic influence registered by the presence of planktonic foraminifera and calcispheres, but also contain rudistid and echinodermal grains: above and below are typical peritidal carbonates. In one section the stage boundary is drawn within the deeper-water facies, in another it is tentatively placed within overlying oncoid-rich packstones and wackestones. These results spotlight the potential use of carbon isotopes as a dating and high resolution correlative tool in shallow-water carbonate rocks, and help elucidate the timing of oceanographic events that affected the Adriatic/Dinaric carbonate platform. In particular it is suggested that the highest rate of relative, possibly eustatic sea-level rise took place during the latest Cenomanian, that this was followed by the global oceanic anoxic event during Cenomanian-Turonian boundary time, and that peak transgression or maximum flooding was achieved during the early to mid-Turonian.